Problemy sudeistva v sportivnoi gimnastike - Teryukina, R. N. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to reveal the reasons of refereeing's mistakes in gymnastics. As a result of this study the factors that can influence the quality of refereeing had been stated. The author offers some new ideas for valuation of refereeing's quality in gymnastics competitions.